Copper - Dameron, C; Howe, P. D (WHO, 1998)
This book evaluates the risks to human health and the environment posed by exposure to copper a malleable metal found naturally in a wide variety of mineral salts and organic compounds and in the metallic form. Copper is an essential element for all biota. It is widely used in cooking utensils and water distribution systems in fertilizers, bactericides, fungicides, algicides, and antifouling paints and in animal feed additives and growth promoters. Industrial applications include use as an activator in froth flotation and sulfide ores in the production of wood preservatives in electroplating and in the manufacturing of azo-dyes.
Environmental health criteria, ISSN 0250-863X No. 200
Keywords: měď; Occupational Exposure; Environmental Exposure; environmentální vědy; pracovní expozice; vystavení vlivu životního prostředí; toxikologie; Copper